2010
DOI: 10.12968/jpar.2010.2.8.78011
|View full text |Cite
|
Sign up to set email alerts
|

Starting young: the challenge of developing graduates' road readiness

Abstract: Australian universities, the majority of paramedic undergraduates tend to come straight from school and many programs are unable to offer early or lengthy on-road placements. This was cited as a cause of the immaturity and poor interpersonal skills raised repeatedly in focus group discussions in a year-long study of paramedic education in Australian universities. Focus groups struggled to label the missing factor in university educated paramedics. A deficit of soft skills was widely suggested, but the phrase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It has been suggested that younger adults lack life experience, awareness of diverse communities in which they will work, and interpersonal skills [ 6 , 7 ]. The median age of paramedics students in Victoria, Australia was 21 years in 2015 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that younger adults lack life experience, awareness of diverse communities in which they will work, and interpersonal skills [ 6 , 7 ]. The median age of paramedics students in Victoria, Australia was 21 years in 2015 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional interpersonal communication skills are essential as they allow for the development of clinician-patient rapport, which facilitates the sharing of information, compliance with treatment and overall patient satisfaction [ 12 14 ]. While educators endeavour to teach the value of interpersonal communication and the associated skills, the links between this and patient outcomes is poorly established upon graduation [ 6 , 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a suggestion that novice paramedics, who are generally in their early 20s, lack understanding, and the ability to communicate effectively with older patients. 20 Finally, providing care and compassion to patients in crisis on a daily basis can take an emotional and psychological toll on paramedics. 21 This can lead to some paramedics experiencing compassion fatigue and choosing consciously, or subconsciously, to not emotionally invest themselves into the complex psychosocial issues of patients as a self-protective mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Both paramedics and GP registrars are more isolated and autonomous in their practice than nurses. The advanced life support skills that GPs find hard to acquire and maintain are also the core business of paramedic practice, yet on the other hand paramedics often have poor communication skills (13)(14)(15), while GPs excel in therapeutic conversation. Our presumption that knowledge exchange could be readily observed where two professions -GPs and paramedics -had such diverse strengths, was correct.…”
Section: Discussionmentioning
confidence: 99%